Evaluating the Effectiveness of Outcome-Based Curriculum Implementation in Improving 21st-Century Skills Among Secondary School Students - Sirojuddin Abror; Tsediso Robert Makoelle (CV. Gerasi Insan Nusantara, 2025)
The demands of the 21st century require educational systems to equip students with critical competencies such as creativity, critical thinking, communication, collaboration, and digital literacy. To meet these demands, many educational institutions have adopted an Outcome-Based Curriculum (OBC) framework, designed to ensure that learning outcomes are measurable, competency-driven, and aligned with future workplace requirements. This study aims to evaluate the effectiveness of OBC implementation in enhancing 21st-century skills among secondary school students. Employing a qualitative library research approach, this study synthesises findings from 55 international peer-reviewed journals, academic books, and policy documents published between 2018 and 2024. The findings reveal that schools implementing OBC demonstrate significant improvements in students’ problem-solving skills, creativity, and collaborative learning outcomes. Furthermore, integrating OBC with digital learning tools and student-centred pedagogies enhances engagement and prepares students to adapt to rapidly changing global challenges. The results underscore the importance of professional teacher training, adequate learning resources, and robust assessment frameworks to ensure successful OBC implementation.